If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + -4 = -3 Reorder the terms: -4 + 2d = -3 Solving -4 + 2d = -3 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2d = -3 + 4 Combine like terms: -4 + 4 = 0 0 + 2d = -3 + 4 2d = -3 + 4 Combine like terms: -3 + 4 = 1 2d = 1 Divide each side by '2'. d = 0.5 Simplifying d = 0.5
| 6x-15+4x+8=3x+9+7x-16 | | 3x+20=1500 | | 2g+7=15 | | -11+2x=19+3x | | 24x+11=123 | | -20+13x=22+11x | | 3c+2p=78 | | X-9=-3+8 | | 2b+1=-9 | | 2*-1.6+6y=-12 | | -3(7m+4)=20-5m | | 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A | | 5y-3=-15 | | 25x+0.6=-30 | | 2q^2-12q=0 | | 2b+-8=2 | | 36+7n=6(5n+6)+3n | | 2(8m+3)=54 | | 2y+2=4x-2 | | 4z-7=11-2z | | 3a+2b-8a-3b= | | 7y-9=4y-12 | | 5r+20-7r=-16 | | -12-2x=-2(x+5) | | s=550 | | 6x+8x+10x=180 | | 12=3(6t+1) | | -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= |